1953
DOI: 10.1063/1.1698626
|View full text |Cite
|
Sign up to set email alerts
|

Regularities in the Spectra of Molecular Complexes

Abstract: The intense so-called ``intermolecular charge-transfer spectra'' shown by a large number of molecular complexes in solution are found to exhibit certain regularities in regard to wavelength and intensity. The wavelengths of these transitions show an excellent correlation with the ionization potentials of the electron donor partners of the complexes. The intensities of the charge-transfer transitions are markedly dependent on the electron acceptor partner of the complex. These results are examined in terms of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

1967
1967
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(56 citation statements)
references
References 12 publications
2
52
0
1
Order By: Relevance
“…It has been reported that the ionization potential of the electron donor may be correlated with the charge transfer transition energy of the complex. 32 Comparison of the transition energies of the CTC in different solvents with the I p values of the electron donors in the corresponding solvents forming the complex reveals a regular relationship, which is in accord with the results obtained by McConnel et al 33 Further evidence for the nature of CT-interaction in the present systems is the calculation of the dissociation energy (W) of the charge transfer excited state of the complex in different solvents. Hence the dissociation energies of the complex were calculated from their CT-energy (hν CT ), I p and E A of the acceptor using the empirical relation given in eqn (5).…”
Section: Ionization Potential Of the Donorsupporting
confidence: 88%
See 1 more Smart Citation
“…It has been reported that the ionization potential of the electron donor may be correlated with the charge transfer transition energy of the complex. 32 Comparison of the transition energies of the CTC in different solvents with the I p values of the electron donors in the corresponding solvents forming the complex reveals a regular relationship, which is in accord with the results obtained by McConnel et al 33 Further evidence for the nature of CT-interaction in the present systems is the calculation of the dissociation energy (W) of the charge transfer excited state of the complex in different solvents. Hence the dissociation energies of the complex were calculated from their CT-energy (hν CT ), I p and E A of the acceptor using the empirical relation given in eqn (5).…”
Section: Ionization Potential Of the Donorsupporting
confidence: 88%
“…Hence the dissociation energies of the complex were calculated from their CT-energy (hν CT ), I p and E A of the acceptor using the empirical relation given in eqn (5). 33 hν…”
Section: Ionization Potential Of the Donormentioning
confidence: 99%
“…The ionization potential Ip of 2T2T can be evaluated (Ip = 8.75 ± 0.01 e.v.) using the relationships between the ionization potential and maxima frequency of the charge transfer band as described by McConnel and Hastings (7,8). …”
Section: Chemical Experimentsmentioning
confidence: 99%
“…The comparison of the position of absorption bands with the ionization potential of the donor was found by McConnell, Han and platt [16,17] to facilitated by a equation (6) that was linear for ionization potential between (7-13) eV. Where (hνCT) is transition energy for CT band, (C1 and C2) are physical constant parameters of electron acceptor in the solvent (C1=0.51eV and C2=1.27eV 2 in ethanol solvent) [7,11].…”
Section: Resultsmentioning
confidence: 99%